A study of the environmental factors influencing the growth phases of Ulva prolifera in the southern Yellow Sea, China. (October 2018) - Jin, Song; Liu, Yongxue; Sun, Chao; Wei, Xianglin; Li, Huiting; Han, Zhen
Abstract: Macroalgal blooms of U. prolifera in the southern Yellow Sea (SYS) have become an ecological disaster. In this study, we attempt to explore the influence of environmental factors and human activity on the annual development of U. prolifera during 2011–2016, combining geostationary ocean color imager images and monitored environmental factors. Blooms of U. prolifera were mainly distributed in the central SYS, drifting from the southern Yellow Sea Radial Sand Ridges. Three growth phases were defined (initial phase, outbreak phase and dissipation phase) to facilitate analysis of the relationship between the environmental factors and growth conditions of U. prolifera . Seaweed cultivation, sea surface temperature (SST) and available radiation influenced the algal biomass during the initial phase; the seawater transparency, precipitation and wind activity affected the algae during the outbreak phase; and SST, intense radiation and cleanup operations increased the rate of algal extinction in the dissipation phase. Highlights: The severity of Ulva prolifera hazard presents an aggravating tendency. Three growth phases of Ulva prolifera are defined. Exploring the influencing factors to the development of Ulva prolifera annually